Total Esophageal Gastric Dissociation for the Failed Antireflux Procedure in a Child with Microgastria - Kengo Hattori; Bruce Bvulani; Alp Numanoglu; Sharon Gail Cox; Alastair J. W. Millar (European Journal of Pediatric Surgery Reports, 2016)
Abstract Microgastria is a very rare anomaly characterized by a very small tubular stomach that presents with severe gastroesophageal reflux disease due to the small reservoir capacity of the stomach. We present a patient with microgastria-related reflux and a failed fundoplication who was treated with total esophageal gastric dissociation (TEGD) resulting in an excellent outcome. In our experience with this good long-term result, we would suggest that TEGD be added to the armamentarium of procedures that can be used in the treatment of microgastria.